2010
DOI: 10.1111/j.1748-0361.2010.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Sources and Mortality Rates Across Rural-Urban Areas in the United States

Abstract: The association between pollution sources and mortality risk is not a phenomenon limited to metropolitan areas. Results carry policy implications regarding the need for effective environmental standards and monitoring. Further research is needed to better understand the types and distributions of pollution in rural areas, and the health consequences that result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 21 publications
4
35
0
Order By: Relevance
“…The main limitations result from definitions used in our analysis and the NSDUH. Our definition of nonmetropolitan counties as ''rural'' diminishes the complexity and differences within rural communities, though this definition is an established method used in prior studies (28,29,51,52). Rurality can be been defined by different measurements -such as population size or density, degree of urbanization, adjacency and relationship to a metropolitan area, principal economic activity, economic and trade relationships, and work commutes -leading to different outcomes (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitations result from definitions used in our analysis and the NSDUH. Our definition of nonmetropolitan counties as ''rural'' diminishes the complexity and differences within rural communities, though this definition is an established method used in prior studies (28,29,51,52). Rurality can be been defined by different measurements -such as population size or density, degree of urbanization, adjacency and relationship to a metropolitan area, principal economic activity, economic and trade relationships, and work commutes -leading to different outcomes (53).…”
Section: Discussionmentioning
confidence: 99%
“…Counties outside of a metropolitan statistical area (RUCC ¼ 4-9) have been categorized into ''nonmetropolitan counties.'' Similar to other peer-reviewed literature, we use ''urban'' to refer to the metropolitan counties and ''rural'' to refer to nonmetropolitan counties (28)(29)(30)(31).…”
Section: Main Independent Variable Of Interest -County Of Residencementioning
confidence: 99%
“…Long-term exposure to polluted water and soil can have serious environmental consequences as well as health hazards such as diarrhea, abortion, hepatitis A, and typhoid (Bagla, 1996;Cutler and Miller, 2005;Boyle, 2007;Hendryx et al, 2010;Zhang et al, 2010;Grant et al, 2012;Naik and Stenstrom, 2012;Kelepertzis, 2014). Heavy metals, nitrites and organic pollutants in contaminated water and soil could increase the potential risk of cancers (Montesano and Hall, 2001;Hansen et al, 2003;Galiani et al, 2005;Wild et al, 2006;He, 2013).…”
Section: Pollution Related Health Risks In Food Production Basesmentioning
confidence: 99%
“…For example, many studies have found that minority groups tend to be exposed to higher levels of environmental hazards (23, 24). In addition, women from urban and rural areas may have very different environmental exposures (25, 26). These differences may imply that exclusion of women with certain characteristics from an epidemiological study may significantly affect the results, especially when they have also been found to have higher risk of adverse health outcomes as previously discussed.…”
Section: Discussionmentioning
confidence: 99%